PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) (STUDI KASUS PADA PROYEK PRESERVASI DAN PELEBARAN JALAN KOTA TAKENGON – SP. UNING – UWAQ) - Tambok Siahaan; Sofyan M. Saleh; Hafnidar A. Rani (Prodi Magister Teknik Sipil Unsyiah, 2020)
This study aims to determine the level of awareness of workers and project personnel, that is, Company Employees, Supervision Consultants, and Owner and analyze the application of OSHMS in the project of Preservation and Road Widening Project of Takengon City Road - SP. Uning - Uwaq. Data analysis was carried out based on indicators that were grouped into 5 (five) OSHMS dimensions and data processing techniques were carried out by observation and 2 (two) questionnaire stages, that is, questionnaire stage l (one) with direct interviews (open) addressed to key informants and questionnaires 2 (two) directed to all Personnel on the project location. It shows that the majority of human resources at the project location have implemented the OSHMS in accordance with the stipulated provisions and project personnel have been excellent, namely 91.6% of respondents answered the analysis based on the dimensions of responsibility and company commitment has been done, 92.5% of respondents answered that the analysis based on the dimensions of policy and K3 discipline has been implemented, 93.7% of respondents answered that analysis based on dimensions K3 communication and training had been carried out, 94.8% of respondents answered that the analysis based the dimensions of the inspection and investigation of work accidents had been carried out, and 94.8% of respondents answered the analysis based on the evaluation dimensions. It can be proven by the existence of various K3 programs, company commitments, APO Procurement, OSH training, health examination services, and Safety promotions that have been carried out at the project site.